PECULIARITIES OF PROFESSIONAL DEVELOPMENT OF EDUCATORS ON THE BASIS OF HUMAN-CENTERED AND CHILD-CENTERED APPROACHES - Kharkivska , A. (Problems of Engineer-Pedagogical Education, 2022)
In the article the author analyzes the features of professional development of educators on the basis of human-centered and child-centered approaches. It was found that the implementation of the ideas of personaldevelopmental education raises the question of the need for compliance of professional qualifications of nursery school teachers with modern world trends in the development of higher pedagogical education. The essence of the concept “competence” as well as the concept “educational competence” is defined as an assessment category that characterizes the teacher as a subject of educational activities in the education system and requires professionalism, pedagogical knowledge, skills, professional positions and attitudes necessary for an active and productive professional activity. In the context of the study, it was proved that pedagogical interaction with preschool children is extremely necessary in the activities of educators, which directly reflects a special form of communication between the subjects of the educational process, including the educator and the child. This is a direct contact between the educator and the preschooler, which affects the formation of the child’s personality, their development and upbringing, behavior, feelings and emotional state, and so on. The author of the article notes that human-centered and child-centered approaches in pedagogical design are based on the need to create conditions for self-improvement and wholesome development of all participants in pedagogical interaction through knowledge of human nature and patterns of their development. Accordingly, there is a development and enrichment of intellectual abilities of subjects of educational activity, their creative thinking and energy for creative activity, spiritual and moral forces, development of value orientations, which is the main purpose of the projected transformations. The paper proves the relevance of using the method of pedagogical design on the basis of human-centered and child-centered approaches, which are the basis of the project structure, which provides binding goals and objectives, description of expected outcomes, audit of available resources, etc. It is clear that the problem of personal and professional growth is one of the current problems of educational science in general and educational professional activity in particular. The author concludes that the most important conditions for the harmonious development of preschool children are the personal professional growth of future nursery school teachers on the basis of human-centered and child-centered approaches. Thus, the main task in the process of professional development of nursery school teachers for preschool children is to help preschool children develop life competence, ideals, values, improve their abilities and so on.